Performance evaluation of different solar advanced oxidation processes applied to the treatment of a real textile dyeing wastewater - Diego R. Manenti (2014)
The performance of different solar-driven advanced oxidation processes (AOPs), such as TiO2/UV, TiO2/H2O2/UV, and Fe2+/H2O2/UV-visible in the treatment of a real textile effluent using a pilot plant with compound parabolic collectors (CPCs), was investigated. The influence of the main photo-Fenton reaction variables such as iron concentration (20-100 mg Fe2+ L-1), pH (2.4-4.5), temperature (10-50 °C), and irradiance (22-68 WUV m-2) was evaluated in a lab-scale prototype using artificial solar radiation. The real textile wastewater presented a beige color, with a maximum absorbance peak at 641 nm, alkaline pH (8.1), moderate organic content (dissolved organic carbon (DOC) = 129 mg C L-1 and chemical oxygen demand (COD) = 496 mg O2 L-1), and high conductivity mainly associated to the high concentration of chloride (1.1 g Cl- L-1), sulfate (0.4 g SO 4 2 - L- 1), and sodium (1.2 g Na+ L-1) ions. Although all the processes tested contributed to complete decolorization and effective mineralization, the most efficient process was the solar photo-Fenton with an optimum catalyst concentration of 60 mg Fe2+ L-1, leading to 70 % mineralization (DOCfinal = 41 mg C L-1; CODfinal < 150 mg O2 L-1) at pH 3.6, requiring a UV energy dose of 3.5 kJUV L-1 (t30 W = 22.4 min; (Formula presented.); (Formula presented.)) and consuming 18.5 mM of H2O2. (c) 2014 Springer-Verlag Berlin Heidelberg.